Characteristics and outcomes of health and social care workers testing positive for SARS-CoV-2 in the Tayside region of Scotland - Siddiqui, Moneeza K. (Eur Respir J, 2020)
Tayside, Scotland was one of the first health boards to institute testing for all symptomatic workers. As expected, there was a high prevalence of SARS-CoV-2 among health and social care workers; however, in most cases disease was mild. https://bit.ly/38JaUmB